2019
DOI: 10.1186/s12883-019-1296-4
|View full text |Cite
|
Sign up to set email alerts
|

Tapping-lips aggravated interictal bilateral discharges in EEG in the patients with Rett syndrome: a case report

Abstract: Background Rett syndrome (RTT) is a severe neurodevelopmental disorder mainly affecting females. One of the main clinical manifestations is hand stereotypies, which is presumed to based on dysfunction rather than on structural impairment. Reflex interictal discharge precipitated by tapping-lips in electroencephalogram (EEG) is a rare phenomenon among RTT. Case presentation We firstly reported a case of RTT concerning interictal reflex discharge precipitated by tapping- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…CTS can be suggested to reflect altered excitability of the perisylvian cortical areas that may contribute to motor and speech disturbances in RTT patients. Evidence for the relevance of CTS to motor control comes from studies that found a suppression of focal CTS by hand tapping/clapping in a subgroup of patients with RTT with six representative cases described in the literature [ 60 , 61 , 75 , 93 ]. In line with these observations, Cooper and colleagues reported a decrease in EEG abnormality during hyperventilation that is accompanied by increased movement in young girls with RTT [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTS can be suggested to reflect altered excitability of the perisylvian cortical areas that may contribute to motor and speech disturbances in RTT patients. Evidence for the relevance of CTS to motor control comes from studies that found a suppression of focal CTS by hand tapping/clapping in a subgroup of patients with RTT with six representative cases described in the literature [ 60 , 61 , 75 , 93 ]. In line with these observations, Cooper and colleagues reported a decrease in EEG abnormality during hyperventilation that is accompanied by increased movement in young girls with RTT [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, in some cases CTS can be precipitated by specific movements. In a case reported by Luo and colleagues, CTS were only induced by right hand-to-lips tapping but not by right hand tapping cheek or abdomen, the left hand tapping lips or observer’s hand tapping the lips [ 60 ]. Roche Martínez and colleagues reported three epileptic Rett patients with reflex seizures triggered by food intake or proprioception [ 66 ].…”
Section: Resultsmentioning
confidence: 99%